Examining the independent and moderating effects of arterial stiffness and cerebral blood flow on total hippocampal and hippocampal subfield volumes - Michelle Horan; Michelle Horan; Daniel Carey; Daniel Carey; Silvin Knight; Silvin Knight; A. Fagan; James F. M. Meaney; James F. M. Meaney; Rose Anne Kenny; Rose Anne Kenny; Rose Anne Kenny; et al. (Frontiers in Aging Neuroscience)
IntroductionThere is a critical link between vascular disease and the progression to dementia. The hippocampus has been implicated in memory and cognitive decline. In this study, we investigate the independent and moderating effects of increased arterial stiffness (AS) and reduced cerebral blood flow (CBF) on hippocampal volume (HV) in a large MRI sample of community-dwelling older adults from the Irish Longitudinal Study on Ageing (TILDA).MethodsLongitudinal data from study participants for Wave 1 (2009–2011) and Wave 3 (2014-2015) were included. This included health and social information as well as a nurse-administered health assessment. Patients who had complete AS, CBF and MR-hippocampal measurements were included. Pseudo-continuous arterial spine labelling was performed to quantify whole CBF. Volumetric analysis was performed using FreeSurfer 6.0 recon-all processing pipeline.Results395 patients met inclusion criteria. This four-year follow up longitudinal study demonstrated that (i) prolonged elevated AS (at wave 1 and wave 3), (ii) the interaction between higher AS at wave 1 and lower CBF at wave 3 and (iii) the interaction between prolonged elevated AS (at wave 1 and wave 3) and reduced CBF at wave 3 were associated with smaller HV.ConclusionIncreased arterial stiffness and reduced CBF were not independently associated with smaller HV. However, in combination, persistently elevated AS and reduced CBF is associated with smaller HV. These effects were equally exerted across all hippocampal subfields tested. Our findings suggest a lag effect in the arterial stiffness and hippocampal volume relationship. We propose that the subsequent reduction in cerebral blood flow observed with elevated arterial stiffness may be the missing link in the pathway associating arterial stiffness with hippocampal atrophy.